(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
This scientific article analyzes innovative processes in the education system, digital transformation, the development of modern pedagogical technologies, and their impact on the effectiveness of education. It also highlights the advantages and disadvantages of an ICT-based educational environment and addresses the issue of digital competencies.